Manajemen Perawatan Pasien Hipertensi Kelompok Usia Dewasa-Very Old Berbasis Family Centered Nursing Di Masa Transisi Endemi Covid-19 - Susanto, Akhiyan Hadi; Utami, Yulian Wiji; Wisnasari, Shila; Rivaldi, Hengky; Santoso, Adi (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2024)
In the current covid-19 endemic, degenerative diseases still have a high prevalence and morbidity rate, one of which is hypertension. The high prevalence of hypertension can be caused by many factors such as improper lifestyle management that can be prevented by adopting a healthy lifestyle. Adults and elderly with hypertension are encouraged to receive non-pharmacological treatments to minimize risk factors for cardiovascular and other systemic and degenerative diseases. Families have an important role in providing information about hypertension and the risk of complications for patients. Families also have a role in providing appropriate care, especially during the period towards endemic covid-19. Counseling was conducted on patients and their families in Sumberejo Village, Poncokusumo District, Malang Regency. The activity was carried out with an initial examination and counseling consisting of 2 main topics: 1) what is hypertension and 2) hypertension care management by family at home. The results showed an increase in knowledge related to physical activity, high blood control, and the role of the family at home with a score of 70 and joint exercises were routinely carried out every 2 weeks. For the sustainability of the program, coordination was carried out with relevant stakeholders.